Therapeutic and prophylactic potential of organic fermented soybean extract against plumbum-induced zebrafish via NMR metabolomics approach - Chong, Siok Geok (2023)
Soybeans (Glycine max) are rich in proteins and isoflavones, with fermentation enhancing their nutritional value but differences between the chemical profiles of organic and non-organic soybeans are unclear. In this study, the chemical profiles of non-organic and organic soybeans and their metabolite changes of the latter after fermentation with Rhizopus oligosporus were investigated using NMR metabolomic approach. A clear separation was only observed between non-organic G and organic Z, which were then selected for further investigation in the fermentation of soybeans (GF and ZF). Even though there were some intensity differences of selected metabolites namely sucrose and citrate, but overall, these most distinctive unfermented soybeans, organic (Z) and nonorganic (G), showed negligible differentiation. Although the chemical compositions between non-organic and organic soybeans exhibited no noticeable differences, the fermentation process undeniably heightened the nutritional value of soybeans. Fermentation enhanced the nutritional value of soybeans, transforming higher sugar content into higher amino acids and organic acids content. The study also explored the potential of fermented soybean extracts (FSE) as an alternative to chelation therapy for mitigating lead (Pb) toxicity as chelation therapy is associated with various side effects and is less effective for patients with low Pb toxicity. Therefore, FSE was evaluated for its therapeutic and prophylactic effect against Pb-induced inflammation in the zebrafish model using NMR metabolomic approach. Preliminary studies were done on various Pb and FSE concentrations with additional support from behavioural assessment (open field test) and transmission electron microscope (TEM). The behaviour of zebrafish altered after Pb inducement and the differential metabolites were increased and decreased in low (5 mg/L) and high (10 mg/ L) Pb concentrations, respectively. Whereas for FSE, the 50 mg/L group significantly alter the four metabolites of sn-glycerol-3-phosphocholine, glucose, isoleucine and glutamine and did not exhibit any necrosis-like cell death in TEM results as the 300 mg/L did. The 50 mg/L dosage of FSE exhibited particularly promising results, demonstrating a small ameliorative effect against Pb-induced inflammation. These results suggested that FSE potentially retrieves the effect of Pb toxicity. Therapeutic measures are essential once damage occurs, however, prophylactic approaches would be better in preventing damage from occurring in the first place and help avoid the potentially serious and long-term health consequences. The potential prophylactic effect of FSE against Pb-induced inflammation on zebrafish was studied using different groups, including a control group without any pre-treatment of FSE and without Pb-induction (N), a placebo group without any pre-treatment of FSE before Pb-induction (N+Pb), and pre-treated groups that were pre-treated with FSE before Pb-induction (FSE+Pb). Mortality was observed in the N+Pb group shortly after 24-h Pb induction at 95dpf, but not in the FSE+Pb group. The N+Pb group showed increased lactate and decreased glutamate and isoleucine levels, indicative of Pb-induced inflammation. At 95dpf, Pb induction triggered the synthesis of glutathione, and its level increased in the N+Pb group but decreased in the FSE+Pb group. At 120dpf, after 24 days in Pb-free conditions, inflammation persists due to the residual Pb, and the level of glutathione depleted in the N+Pb group but elevated in the FSE+Pb group. Although both N+Pb and FSE+Pb underwent Pb induction at the same time, but difference in glutathione levels suggests that FSE possesses a prophylactic effect that lessens the inflammatory effect of Pb toxicity. In short, this research analysed the chemical profiles of organic and non-organic soybeans and the effects of fermentation and found that fermentation enhances their nutritional value. Fermented soybean extracts showed potential in alleviating lead (Pb) toxicity in a zebrafish model. Prophylactic approaches, like using fermented soybean extracts, demonstrated better results in preventing inflammation due to Pb toxicity compared to therapeutic interventions.